Karakteristik Subjektif Tidur Klien Rawat Inap Dewasa Di Rumah Sakit X Depok - Rahma Marfiani; Hening Pujasari (Fakultas Ilmu Keperawatan Universitas Indonesia, 2015)
Penelitian ini mengenai karakteristik subjektif tidur pada klien rawat inap dewasa di Rumah Sakit X Depok. Desain penelitian ini deskriptif sederhana dengan pendekatan cross-sectional. Sampel yang terlibat berjumlah 72 pasien dengan teknik pengambilan sampel consecutive sampling. Responden mengisi kuesioner berisi skala tidur Verran dan Snyder-Halpern. Hasil penelitian didapatkan bahwa pasien mengalami gangguan tidur tingkat sedang (47,22%) hingga berat (25%). Efektivitas tidur pasien juga hanya berada pada tingkat sedang (50%) hingga rendah (19,44%). Pasien juga mensuplementasikan tidurnya dengan tingkatan sedang (38,88%) hingga tinggi (22%). Penelitian ini dapat digunakan sebagai penelitian dasar untuk meneliti faktor-faktor yang memengaruhi pola tidur pasien rawat inap. Abstract Sleeping Subjective Characteristics of Adult Patient at X Hospital Depok. This research explored subjective sleep characteristics of hospitalized adult patients in X Hospital Depok. Simple descriptive design was used in this research. Consecutive sampling was applied on this study involving 72 patients. Patients were asked to fill the questionnaire about Verran and Snyder Halpern sleep scale (VSH Sleep Scale). Results showed that patients experienced sleep disturbance with moderate levels (47,22%), moreover (25%) patients experienced severe sleep disturbance. Patients felt that sleep effectiveness in moderate levels (50%), moreover (19,44%) patients felt that sleep effectiveness only in low levels. Sleep supplementation also experienced by patients with moderate levels (38,88%), moreover (22%) patients experienced sleep supplementation in high levels. This research can be used as a pilot study to find out factors that affecting how patients sleep in the hospital environment. Keywords: adult patients, hospitalized, subjective sleep characteristics, VSH Sleep Scale